2017
DOI: 10.1007/s11011-017-0106-1
|View full text |Cite
|
Sign up to set email alerts
|

Epileptic seizures in nonalcoholic Wernicke’s encephalopathy: a case report and literature review

Abstract: Wernicke encephalopathy (WE) is characterized by eye signs, cerebellar dysfunction, and confusion. Epileptic seizures are rare in nonalcoholic WE. We reviewed the clinical, laboratory, radiological, and prognostic characteristics of nonalcoholic WE accompanied by epileptic seizures. We reported 1 case and searched similar cases using PubMed, WoK, Ovid, and Embase. WE was diagnosed according to dietary deficiencies, clinical symptoms and brain magnetic resonance imaging (MRI). We reviewed 13 patients (median ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Till date only 13 cases have been reported due to non-alcoholic WE presenting with epileptic seizures in literature. [ 6 ] Only two of them presented with seizures as an initial manifestation (our case is the third reported case in this regard) and only six of those cases had cortical lesions (ours is the seventh being reported). In our case, both cortical and bilateral thalamus involvement explained the source of seizure activity even in the absence of any demonstrable electrolyte imbalance.…”
Section: Discussionmentioning
confidence: 68%
“…Till date only 13 cases have been reported due to non-alcoholic WE presenting with epileptic seizures in literature. [ 6 ] Only two of them presented with seizures as an initial manifestation (our case is the third reported case in this regard) and only six of those cases had cortical lesions (ours is the seventh being reported). In our case, both cortical and bilateral thalamus involvement explained the source of seizure activity even in the absence of any demonstrable electrolyte imbalance.…”
Section: Discussionmentioning
confidence: 68%
“…A recent literature review reported 14 cases of nonalcoholic Wernicke’s encephalopathy with seizure. Only six of those displayed cortical involvement [ 1 ]. Among those patients, only three had seizures as the initial presentation.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that this is a good case to report as a seizure as the initial presentation of WE was reported only in 14 cases in the English literature. This case also shows that early thiamine replacement can result in significant neurological improvement [1]. In this case report, we aim to review what the English literature has to answer the questions about the differences between alcoholic and nonalcoholic WE, the risk factors of nonalcoholic WE, the typical and atypical MRI findings, and the prevalence of seizure and cortical lesion in WE.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, cases of Wernicke encephalopathy have been reported, which are epileptic seizures that improve after thiamine treatment. (Fu et al 2017;Shang et al 2017). It has also been suggested that severe thiamine de ciency may cause epilepsy in infants (Fattal-Valevski et al 2009a).…”
Section: Thiamine (Vitamin B1mentioning
confidence: 99%